Towards a Pattern Language for the Design of Collaborative Interactive Systems - Iacob, Claudia; Mussio, Piero; Zhu, Li; Barricelli, Barbara (Electronic Communications of the EASST, 2011)
Nowadays, the design of interactive systems addresses diverse communities of end users, each belonging to a certain culture, having a role in the context/domain and using a specific digital platform. More than often, they come together and collaborate in performing their work tasks and need to be supported by virtual interactive systems. This brings a set of challenges and design problems to be faced by interaction designers focused on the design of collaborative interactive systems. The present paper focuses on one approach to overcome these challenges – by making available the knowledge and wisdom within a team of designers to each and every designer in the team by the definition of pattern languages, organized as sets of multimedia, multimodal documents accessible and manageable in the Web. A design pattern language comprises a set of inter-related design patterns able to address interaction design problems and to allow the accumulation and use of knowledge within a team of designers. This paper identifies and describes a set of design patterns addressing the design of collaborative interactive systems together with the possible relationships among them and the operations made available to designers for managing and using the patterns.